Phosphorothioated antisense oligodeoxynucleotide suppressing interleukin-10 is a safe and potent vaccine adjuvant. Issue 30 (9th July 2019) - Zhang, Jin; Liu, Ninghua; Lu, Yang; Huang, Zhen; Zang, Yuhui; Chen, Jiangning; Zhang, Junfeng; Ding, Zhi
Abstract: While vaccination is highly effective for the prevention of many infectious diseases, the number of adjuvants licensed for human use is currently very limited. The aim of this study was to evaluate the safety, efficacy, and to clarify the mechanism of a phosphorothioated interleukin (IL)-10-targeted antisense oligonucleotide (ASO) as an immune adjuvant in intradermal vaccination. The cytotoxicity of IL-10 ASO and its ability to promote T cell proliferation were assessed by Cell Counting Kit-8 (CCK-8) assay. The contents of IL-6, IL-8, TNF-α, IL-1β, and IL-10 in inoculated local tissue and the antigen-specific antibody titers in mouse serum samples were determined by ELISA. The target cells of IL-10 ASO were observed using immunofluorescent staining. The results showed that the specific antibody titer of ovalbumin (OVA), a model antigen, was increased 100-fold upon addition of IL-10 ASO as an adjuvant compared to that of OVA alone. IL-10 ASO showed an immunopotentiation efficacy similar to that of Freund's incomplete adjuvant, with no detectable cell or tissue toxicity. In vitro and in vivo experiments confirmed that IL-10 ASO enhances immune responses by temporarily suppressing IL-10 expression from local dendritic cells and consequently promoting T cell proliferation. In conclusion, IL-10 ASO significantly enhances immune responses against co-delivered vaccine antigens with high efficacy and low toxicity. It has the potential to be developed into a safe and efficient immune adjuvant.